Exploring frames that provide opportunities for learning by teaching, learning by reflecting and learning by collaborating: case studies of pre-service teachers - De Kock, Cisca (Stellenbosch : Stellenbosch University, 2023)
Thesis (DEd )--Stellenbosch University, 2023.